And: A Complex Little Word at the Heart of Janet Frame’s Language - Wilfrid Rotgé (Angles)
The aim of this paper is to provide an explanation of Janet Frame’s short story “The Birds Began to Sing” through a detailed study of the grammatical marker “and”, using concepts borrowed from cognitive grammar and the “theory of enunciation”. It also attempts to show how linguistic theory can be applied to a literary text, which is not used just as a linguistic corpus but analyzed in its literary specificity. The coordinator “and”, which is often perceived semantically as well as stylistically as unimportant, lies at the heart of Janet Frame’s short story. It gives it meaning and reveals an underlying complexity beneath the short story’s apparent simplicity and ultimately false naivety.